Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our User Agreement and Privacy Policy.

Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our Privacy Policy and User Agreement for details.

Like this presentation? Why not share!

- Complex Numbers by itutor 7035 views
- solving quadratic equations using q... by maricel mas 6836 views
- Systems of Linear Equations Graphing by PLeach 4299 views
- Quadratic equation by HOME! 17784 views
- Multiplying Monomials by Pinky Faith 20881 views
- 7.7 Solving Radical Equations by swartzje 24286 views

No Downloads

Total views

16,068

On SlideShare

0

From Embeds

0

Number of Embeds

11,183

Shares

0

Downloads

84

Comments

0

Likes

4

No embeds

No notes for slide

- 1. Solving Quadratic Equations By Completing the Square
- 2. What is a Perfect Square Trinomial?
- 3. How to create a Perfect Square Trinomial <ul><li>In the following perfect square </li></ul><ul><li>trinomial, the constant term is missing. </li></ul><ul><li>x 2 + 14x + ____ </li></ul><ul><li>Find the constant term by squaring half </li></ul><ul><li>the coefficient of the linear term. </li></ul><ul><li>(14/2) 2 </li></ul><ul><li>X 2 + 14x + 49 </li></ul>
- 4. Perfect Square Trinomials 100 4 25/4
- 5. How to “Complete the Square” Solve the following equation by completing the square: x 2 + 8x – 20 = 0 Step 1: Move quadratic term, and linear term to left side of the equation x 2 + 8x = 20
- 6. Step 2: Find the term that completes the square on the left side of the equation. Add that term to both sides. x 2 + 8x + ? = 20 + ? x 2 + 8x + 16 = 20 + 16 8/2 = 4 4 2 = 16
- 7. Step 3: Factor the perfect square trinomial on the left side of the equation. Simplify the right side of the equation.
- 8. Step 4: Take the square root of each side and solve. x = 10 or x = -2
- 9. Example #2 2 2 2
- 10. Step 2: Find the term that completes the square on the left side of the equation. Add that term to both sides. x 2 – 7/2 + 49/16 = -6 + 49/16 x 2 – 7/2 + 49/16 = -96/16 + 49/16 x 2 – 7/2 + 49/16 = -47/16 ½ * 7/2 = 7/4 (7/4) 2 = 49/16
- 11. <ul><li>x 2 – 7/2 + 49/16 = -47/16 </li></ul><ul><li>(x -7/2)(x -7/2) = -47/16 </li></ul><ul><li>(x – 7/2) 2 = -47/16 </li></ul><ul><li>(x – 7/2) 2 = -47/16 </li></ul><ul><li>x -7/2 = i 47 </li></ul>Step 3: Factor the perfect square trinomial on the left side of the equation Step 4: Take the square root of each side 4 X = 7/2 + i 47 or x = 7/2 - i 47 4 4

No public clipboards found for this slide

Be the first to comment